Filipino English teachers overseas: A case study of the Filipino English teachers’ language ideology - Bautista, Aileen C. (Animo Repository, 2020)
Various studies have presented the complexity of the impact of globalization in shaping the language ideologies of individuals. However, it seems that there is a dearth in the literature that seeks to examine the experience of the Filipino Non-native English-Speaking Teachers (NNESTs). This case study explores how their practice in teaching English abroad has shaped their language ideologies. Specifically, the study investigated the 18 Filipino NNESTs from Japan, Vietnam, Singapore, Indonesia, and Canada. The findings of this study predicated on the assertions of Tupas and Salonga (2016) in their research about the Filipino call center agents where unequal Englishes is observed. However, based on the data gathered, this current study exposed that there is another facet of unequal Englishes existing among the Filipino NNESTs where they seem to be the inherent gate-keepers. Meaning, that their knowledge in the English language has led them to be hypercritical even among themselves and their capabilities as English teachers, which I believe is worse than the usual same-circle privileging posited by Tupas and Salonga (2016). Thus, showing how white privileging has already permeated the system even of the educated Filipino NNESTs, which may be too challenging to correct.